The Typological Peculiarities of the Negative Adverbs of the German Language - Shachilvyan, Naira (Bulletin of Yerevan University B: Philology, 2022)
In this article the typological peculiarities of the negative adverbs of modern German are presented in comparison with the corresponding facts of the Armenian language, which acts here as an etalon language. Negative adverbs are lexicogrammatical means of expressing negation, which are remarkable because their presence in the composition of a sentence contributes to the manifestation of peculiar features of the formation of negative sentences in different languages, as well as at different stages of the development of one language. It is shown that by the abovementioned means of expressing negation the mononegative type of the modern German language is opposed to the polynegative type of the Armenian language. The mononegative system of the German language is usually explained by the general tendency towards the maximum possible combination of grammatical structures in this language. In German negative adverbs may function in a sentence as adverbial modifier of time, place and manner and give a negative meaning to the affirmative form of the predicate and at the same time to the whole statement, performing the function of general negation, while the equivalent means in the Armenian language are used with the same function, as a rule, with negative forms of the verb and act as a complex whole. In Armenian negative adverbs are the main negative elements in a sentence, since their presence necessitates the use of negative forms of the verb, while the opposite fact is not typical here.